Peran Literasi EkonomiDalam Memoderasi Pengaruh Iklan dan Konformitas terhadap Perilaku Konsumtif (Universitas Negeri Semarang, 2022)
This study aims to analyze the effect of advertising and conformity on consumptive behavior with economic literacy as a moderating variable. The population in this study were all active students of the 2017 Semarang State University Accounting Economics Education Study Program, totaling 92 students, all of whom were used as research respondents. Methods of data collection using a questionnaire. The data analysis method used is descriptive statistical analysis and Moderated Regression Analysis (MRA) with absolute difference value test. The results showed that advertising had a positive and significant effect on consumptive behavior by 19.01%. Conformity has a positive and significant effect on consumptive behavior by 25.20%. Economic literacy is not able to moderate the effect of advertising and conformity on consumptive behavior.